Se deben incorporar a la ley de prevención y control de la contaminación ambiental sanciones de carácter económico, multas, que graven a quienes incurran en contravenciones ambientales graves, como: la emisión de gases, el canon de saneamiento del agua, sobre vertidos, sobre depósitos de residuos peligrosos, y sobre instalaciones peligrosas - Gualan, Julio Antonio (2015)
This legal research work addresses a topical issue in the world and particularly in our country, that is, the environmental pollution caused by the commission of environmental offenses as conceptualized by severe environmental laws, such as emission, vehicles, heavy machinery, sugar, etc .; deposits of hazardous waste in streams, rivers, streams, lakes by industrial, factories; hazardous installations with chemicals, radioactive components, nuclear facilities, which involve risks to the environment and nature. Everything annotated set a number of dangers for the preservation of a healthy environment, free from pollution, all derived from environmental laws that have no rules that punish the commission of these grave breaches. This work is approached from the field of environmental law, in relation to the environmental damage caused by fumes and fluctuations in gases and toxic substances, analysis of the constitutional area whose standards set out the principles of protection of nature and the environment of the Law on Prevention and Control of Environmental Pollution, the doctrinal framework of environmental violations and environmental damage, comparative law analysis regarding serious environmental offenses and their punishment. It includes research to develop; a conceptual framework about the environment their different theoretical concepts, definitions of the environment, environmental management, environmental problems at the regional, urban areas, in rural areas, environmental damage their nature, characteristics of environmental damage, responsibility for the damage. Then discusses the legal framework, based on the Constitution of the Republic, with regard to the rights of nature, nature and environment, biodiversity, natural heritage and ecosystems, natural resources; Analysis of the Environmental Management Act; Law on Prevention and Control of Environmental Pollution, comparative law and serious environmental violations. Then doctrinal criteria is analyzed, the environment, the environmental impact; Historical development of environmental law, international environmental law, doctrine and environmental damage. An analysis of the methodological aspect comprising the methodology used, the methods, techniques and procedures used in the research process. Research field or empirical research includes analysis of the results of surveys to a universe of 30 people, as well as interviews five people familiar with the problem of environmental damage